Assessment of soil properties, plant yield and composition, after different type and applications mode of organic amendment in a vineyard of Mendoza, Argentina - Martínez, Laura Elizabeth (2018)
Fil: Martínez, Laura Elizabeth. Universidad Nacional de Cuyo. Facultad Ciencias Agrarias. Mendoza, Argentina.